2020
DOI: 10.2147/hiv.s278855
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dietary Diversity and Associated Factors Among Adult HIV Positive Patients on Anti-Retroviral Therapy in Public Hospitals of Kembata Tembaro Zone, Southern Ethiopia</p>

Abstract: Background: Nutrition is a significant factor in all stages of HIV. Dietary management of HIV-positive patients is key to supporting their capacity to continue participating in the workforce and contributing to socioeconomic growth. Few studies have been conducted regarding this important public health problem of dietary diversity throughout the developing countries including Ethiopia. Therefore, this study assesses the magnitude and factors associated with dietary diversity among HIV-positive patients attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Moreover, due to cultural pressures, people choose to purchase flesh meat rather than organ meat although organs are important micronutrient storage sites (26) . This finding is similar to various previous studies conducted on different study populations in the country and a similar studies in Kenya as well (24,27,28) .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, due to cultural pressures, people choose to purchase flesh meat rather than organ meat although organs are important micronutrient storage sites (26) . This finding is similar to various previous studies conducted on different study populations in the country and a similar studies in Kenya as well (24,27,28) .…”
Section: Discussionsupporting
confidence: 93%
“…Poor dietary diversity was also commonly observed among the adult PLWHA in this study. Undiversified food has always been a public health concern in developing countries [15] and was also found among adult HIV-positive patients in the sub-Saharan region [16]. This puts chronic patients like PLWHA at higher risks as consumption of low-quality and monotonous food can exacerbate the micronutrient and macronutrient deficiencies as their nutrient absorption and metabolism are already adversely affected by the disease [17].…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…This might be because those patients with a low income had no access to sufficient food to meet their dietary needs for productive and healthy life exposing them to deficiency of macro and micronutrients. A study conducted in different parts of Ethiopia [35][36][37] and in Kenya [38] and Rwanda [39] indicated that low average monthly income was associated with a low dietary diversity among HIV/ AIDS patients. In contradict to our finding, that of a study done in Dilla University Referral Hospital in South Ethiopia indicated that moderate poor economic condition is not associated with underweight [40].…”
Section: Plos Onementioning
confidence: 99%